Импрессионизм - Абеляшева Галина Викторовна (История искусства для детей, 2004)
Экземпляры: ДБ (20210111) / Инвентарный номер: 41109 / Цена: 138.33 / Сис.шифр: 85.14ср / Авт.знак: А 14 / ГРНТИ: 18 / ББК: 85.14ср